2017
DOI: 10.1007/s00198-017-3972-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of systemic bone mineral density on atlantoaxial subluxation in patients with rheumatoid arthritis

Abstract: Our study showed a possible association between lower BMD and AAS occurrence in patients with RA with lower BMI. Further studies are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Demineralization was found on radiographs in almost half of the patients. Han et al suggested that patients with low bone mineral density (BMD) and lower body mass index (BMI) have a higher risk of AAS [ 27 ]. Rossini et al suggested that osteoporosis may be an independent risk factor for bone erosions in RA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demineralization was found on radiographs in almost half of the patients. Han et al suggested that patients with low bone mineral density (BMD) and lower body mass index (BMI) have a higher risk of AAS [ 27 ]. Rossini et al suggested that osteoporosis may be an independent risk factor for bone erosions in RA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporotic conditions may lead to atlantoaxial ligament laxity. These conditions may be aggravated in RA patients with a lower BMI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we noted that half of patients with AAS had more frequent extra articular features. To our knowledge, few data in the literature are available regarding the association between cervical spine involvement and osteoporosis during RA (Han et al., 2017; Neva et al., 2006; Uchino et al., 2021). We found that 66% of patients with AAS had osteoporosis ( p = 0.012).…”
Section: Discussionmentioning
confidence: 99%